Техническое черчение: учебное пособие / Г. В. Чумаченко - Чумаченко Галина Викторовна (Серия "НПО", 2005)
Экземпляры: РБ (20180503) / Инвентарный номер: 38856 / Цена: 96.00 / Авт.знак: Ч-90 / ББК: 30.11я722